Does project-based learning enhance Iranian EFL learners’ vocabulary recall and retention? - Shafaei, Azadeh; Abdul Rahim, Hajar (Urmia University, 2015)
Vocabulary knowledge is an integral part of second/foreign language learning. Thus, using teaching methods that can help learners retain and expand their vocabulary knowledge is necessary to facilitate the language learning process. The current research investigated the effectiveness of an interactive classroom method, known as Project-Based Learning (PBL), in helping Iranian EFL learners not just learn but retain new vocabulary knowledge. To this end, an experimental approach using two groups of participants (i.e. experimental and control) was employed. The experimental group was taught using the PBL method while the control group was taught using the conventional method. The findings of the study indicated that learners who were taught using the PBL approach (i.e. the experimental group) had a significant improvement in their vocabulary recall and retention rate. Besides, they even showed better retention of new vocabulary with higher level of difficulty. This supports previous findings on the effectiveness of PBL as a vocabulary teaching method in the EFL context which could contribute to the betterment of the existing teaching methods.